Siasat Mengatasi Perilaku Jujur yang Kian Luntur pada Anak-Anak di Kelompok Belajar Al-Ikhsan - Maswandhani Destriando; Agus Suriadi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Honest behavior is behavior that reflects generosity and loyalty, because by saying and behaving honestly someone will be respected by others. However, lately honest attitudes and behavior have begun to be rarely seen, especially in children. Practicing honesty in children from an early age needs to be done so that later children can grow into good personalities and can be trusted by everyone. Not all things that make children lie are bad things. Sometimes, children can lie because they cannot distinguish between what is true and what is not. In addition, children may also lie for several reasons, namely feeling afraid of being punished, avoiding work or obligations, seeking attention, trying to get something they want. , Fear of disappointing others. There are several impacts that can be received if a child is used to telling dishonest things, namely, by telling dishonest things it will become a bad habit, will be shunned by other people, will always feel suspected, will be shunned and disliked by others. In addition, there are also several tactics or ways so that children can say and behave honestly, including by explaining the good when telling the truth and the bad when saying dishonestly, admonishing in a subtle way, form their mindset, respect the honesty conveyed, teach them to always be grateful. There are several stages carried out in this study including, the Intake Case Stage, the Member Selection Stage, the Assessment and Intervention Planning Stage, the Group Development Stage, and the Evaluation and Termination Stage.